ANALISIS PENENTUAN KUALITAS AIR SUNGAI GESANG DENGAN PARAMETER BOD DAN COD - Zainal Abidin; Farahdilla Andhika Y.F (Jurnal Environmental Science, 2022)
Gesang River has an important role for the residents of Palaan Village and Kesaamben Village, Ngajum District, Malang Regency. This study aims to analyze the water quality of the Gesang River. The method used is a survey method, with a sampel of 6 points. Parameters observed were physics and chemistry (BOD, COD, and TSS). The sampling technique was carried out by purposive sampling and the data analysis used was descriptive qualitative. To campare the water quality of the Gesang River, it is necessary to refer to PP. 82 tahun 2001 and Peraturan Gubernur Jawa Timur No. 72 Tahun 2013. The results of laboratory analysis explain that the water quality of the Gesang River with BOD parameters at points P III, P IV, P V, P VI exceeds the quality standart. On the COD Parameters at points PII, PIV, PV, PVI the highest BOD score was 83,75 mg/L, while the highest COD score was 244,6 mg/L. the pollution load with TSS parameters at 6 points all exceeded the quality standart, with the highest score of 57,5 mg/L. the increased concentration of BOD, COD, dan TSS was caused by the presence of pollution that was found to come from industrial waste, agricultural waste, and household waste. Polluted rivers cause unstable ecosystems and can distrupt human activities. Therefore, continuous is needed between the Palaan Village government, Kesamben and the industry.